A Taguchi approach to synthesise Al/Fe core–shell composite powders through electroless deposition. (3rd September 2021) - Ali, Rashid; Ali, Fahad; Zahoor, Aqib; Shahid, Rub Nawaz; Tariq, Naeem ul Haq; Ullah, Saad; Ahmed, Rizwan; Awais, Hasan Bin
ABSTRACT: In the present study, Al/Fe core–shell particles were successfully synthesised by electroless deposition of iron on aluminium particles. The process variables were investigated and optimised to achieve maximum deposition efficiency. These variables, including chemical composition parameters (molar ratios of salt/reducing agent, salt/complexing agent and pH) and process parameters (particle size, temperature and time) were optimised by using the Taguchi method. The chemical composition of iron deposited aluminium particles, their morphology and coating quality were characterised by helium gas pycnometry, scanning electron microscopy, energy-dispersive spectroscopy and X-ray diffraction. The results revealed that, by using the optimised bath chemical composition and optimised process parameters, a maximum of 28.91% iron deposition on aluminium particles can be obtained within 20 min.